First-principles study on electronic states of In2Se3/Au heterostructure controlled by strain engineering. Issue 17 (11th April 2023) - Han, Sha; Xia, Cai-Juan; Li, Min; Zhao, Xu-Mei; Zhang, Guo-Qing; Li, Lian-Bi; Su, Yao-Heng; Fang, Qing-Long
Abstract : The development of low-dimensional multifunctional devices has become increasingly important as the size of field-effect transistors decreases. Abstract : The development of low-dimensional multifunctional devices has become increasingly important as the size of field-effect transistors decreases. In recent years, the two-dimensional (2D) semiconductor In2 Se3 has emerged as a promising candidate for applications in the fields of electronics and optoelectronics owing to its remarkable spontaneous polarization properties. Through first-principles calculations, the effects of the polarization direction and biaxial tensile strain on the electronic and contact properties of In2 Se3 /Au heterostructures are investigated. The contact type of In2 Se3 /Au heterostructures depends on the polarization direction of In2 Se3 . The more charge transfers from the metal to the space charge region, the biaxial tensile strain increases. Moreover, the upward polarized In2 Se3 in contact with Au maintains a constant n-type Schottky contact as the biaxial tensile strain increases, with a barrier height Φ SB, n of only 0.086 eV at 6% strain, which is close to ohmic contact. On the other hand, the downward polarized In2 Se3 in contact with Au can be transformed from p-type to n-type by applying a biaxial tensile strain. Our calculation results can provide a reference for the design and fabrication of In2 Se3 -based field effect transistors.